(untitled) (International Journal of Environmental Sciences, 2024)
Objective: This study aimed to develop and validate a simple, rapid, sensitive, and cost-effective visible spectrophotometric method for the quantitative determination of Amlodipine Besylate (AMB), Oseltamivir Phosphate (OLP), Pantoprazole Sodium Sesquihydrate (PSH), and Venlafaxine Hydrochloride (VFH) in bulk drugs and commercial tablet formulations. Methods: The method is based on the oxidation of the selected drugs with a known excess of N-Bromosuccinimide (NBS) in hydrochloric acid medium. The residual NBS bleaches Rhodamine-B dye, and the absorbance of the unbleached dye, proportional to the drug concentration, was measured spectrophotometrically. Experimental variables, including acid concentration, reaction time, and reagent volumes, were optimized to achieve maximum sensitivity and reproducibility. Results: The proposed method showed excellent linearity over the selected concentration ranges for all four drugs and was successfully applied to the assay of commercial tablet formulations without interference from common pharmaceutical excipients. Validation, performed according to ICH guidelines, demonstrated excellent accuracy, precision, robustness, ruggedness, and sensitivity, with satisfactory LOD and LOQ values and %RSD below 2%. The assay results were in good agreement with the labelled claims, confirming the suitability of the method for routine quality control of bulk drugs and pharmaceutical formulations.